OSTEOCLASTOMA OF JAW IN CHILDREN: CLINICAL AND MORPHOLOGICAL CHARACTERISTIC - Tkachenko P.І.; Starchenko І.І.; Bilokon S.О.; Gurzhiy О.V.; Mykytenko, V.V.; Bilokon, N.P. (World of Medicine and Biology, 2016)
Morphological features of osteoclastomas have been studied on 26 specimens made from the postoperative material by the staff of the Department of Pathological Anatomy with autopsy according to conventional techniques. The observations showed that osteoclastomas were often diagnosed in boys of junior and senior school age. To define the onset of the tumor development was quite difficult due to asymptomatic, slow and imperceptible nature of its growth. At the same time the complaints of patients differed slightly depending on the localization and the period of the tumors’ onset, mostly regarding the occurrence of asymmetry of the face, growing slowly. Sometimes it was accompanied by painful feelings and signs of dilatation of venous vascular system of the mucosa.